Two level half factorial design for the extraction of phenolics, flavonoids and antioxidants recovery from palm kernel by-product - Wong, W.H.; Lee, W.X.; Ramanan, R.N.; Tee, L.H.; Kong, K.W.; Galanakis, C.M.; Sun, J.; Prasad, K.N. (Elsevier, 2015)
Every year palm oil industry in Malaysia produces enormous quantity of by-products and has great potential to be reutilized as good source of antioxidants. In this study, a two level half factorial design was employed to recover phenolics, flavonoids and antioxidants from palm kernel by-product. The assay included the following independent factors: pH (2-6), ethanol concentration (20-80%), liquid to solid ratio (10-100. mL/g), temperature (30-80. °C) and time (30-300. min). Half factorial design was employed to determine the significant contribution of the above factors towards antioxidant capacity (total antioxidant activity, DPPH and FRAP), total phenolic and flavonoid contents. Among, all the factors examined, ethanol concentration and liquid to solid ratio are very significant (p<0.0001), in obtaining higher antioxidant activity, total phenolic and flavonoid contents. Thus, palm kernel by-product can be proposed to be used as natural antioxidant.